Exploring the change of coastal saline agroecosystem diversity, composition and predicted function of soil microbial community mediated by soybean and corn intercropping - Nyimbo, Witness Joseph; Fallah, Nyumah; Mutombo, Arcel Mulowayi; Xu, Hailong; Bin, Qin; Makungu, Janeth Samwel; Lin, Wenxiong (Frontiers in Plant Science, 2025)
IntroductionSoil microbial community is the key determinant of coastal agroecosystem soil health. However, the response of soil microbial community and its anticipated functions to soybean and corn intercropping in coastal saline agroecosystems is not well understood.MethodSoybean and corn intercropping was done in Putian city of Fujian province. After harvest, soil total carbon (TC), total phosphorus (TP), total nitrogen (TN), total organic carbon (TOC), soil organic matter (SOM), salinity content and elemental ratios of C: N, C: P and N: P were examined. High-throughput sequencing was performed to investigate the community composition and diversity of rhizospheric bacterial and fungal communities as influenced by monoculture soybean (MS) and corn (MC), first (FP) and second (SP) intercropping pattern. LEfSe cladogram was generated to identify potential microbial markers and metagenome was annotated with the metabolic cycles and pathways in the KEGG database to predict the microbial function. The co-occurrence and RDA analysis assessed the correlation between microbes and soil microbes with soil chemical parameters.Results and discussionThe intercropping patterns FP and SP significantly influenced soil TC, TP, TN, SOM, EC, pH and salinity content. The C: N, C: P, and N: P ratios were influenced by C, N, and P concentrations. Our investigation found that Chao1 was significantly higher in intercropping patterns than in monoculture patterns. Nevertheless, the Shannon index was substantially higher in monoculture than in intercropping patterns FP and SP indicating reduced bacterial and fungi diversity measured by species richness and evenness. The Non-Metric multidimensional scaling (NDMS) diversity showed that all samples were significantly clustered into four major groups, according to the bacteria and fungi communities of origin. Further statistical analysis revealed that cropping patterns strongly affected microbial communities. Furthermore, Proteobacteria, Actinobacteria, Acidobacteria, and Chloroflexi were enriched bacterial phyla in the rhizosphere of MS, MC, FP, and SP. Ascomycota, Mortierellomycota, and Basidiomycota were the most enriched fungi phyla in each intercropping pattern. These phyla were identified as sensitive biomarkers for soil nutrient circulation, ecosystem bioremediation and chemical degradation.ConclusionThis study increases our understanding of soybean and corn intercropping in coastal saline agroecosystems microbiomes